Bureaucraic posture: on the need for a composite theory of bureaucratic behavior - Wise, Lois Recascino (2004)
This article examines the underlying assumptions and main findings of four streams of research on bureaucratic postures. It explores the utility of each school of thought for understanding how perspectives on bureaucratic posures are associated with the advancement of the public interest and bureaucratic performance. A main conclusion is that, although limited in scope of application, each stream has merit. Nonetheless, the existing research is too narrow: The field needs to consider a more complex model of bureaucratic behavior that draws from these four fields to offer a framework that is widely applicable to the range of motives for work found in the public bureaucracy and the variety of behaviors that individuals exhibit. Some attributes that may characterize such a model are sketched out. - Reproduced.
Keywords: Civil service